2007
DOI: 10.1002/chem.200601013
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Assembly and Disassembly of Gold Nanoparticles Directed by a Zwitterionic Polymer

Abstract: Herein, we have successfully introduced the stimuli-response concept into the controllable synthesis of gold nanoparticles (AuNPs) with designed properties. We used a pH-responsive zwitterionic polymer that acted as a template and a stabilizer. Gold colloids prepared in situ from the polymer solution have a narrow size distribution of about 5 nm. The assembly and disassembly of AuNPs can be finely tuned by modulating the net charges of the zwitterionic polymer so that they are either positive or negative as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…This is also in agreement with that described in eq. (1) and has been found in many other systems [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . In a previous report, we studied the catalytic activity of GNs supported by core-shell micelles with polystyrene (PS) as core and poly(4-vinylpyrydine) (P4VP) as shell and found that since the GNs on the surface of the micelle were wrapped by collapsed P4VP, their catalytic efficiency decreased with the decrease of GNs on the surface [15] .…”
Section: Responsive Catalytic Activity Of Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also in agreement with that described in eq. (1) and has been found in many other systems [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . In a previous report, we studied the catalytic activity of GNs supported by core-shell micelles with polystyrene (PS) as core and poly(4-vinylpyrydine) (P4VP) as shell and found that since the GNs on the surface of the micelle were wrapped by collapsed P4VP, their catalytic efficiency decreased with the decrease of GNs on the surface [15] .…”
Section: Responsive Catalytic Activity Of Compositesmentioning
confidence: 99%
“…The catalyst of GNs used in this system is so little that its effect on absorbance intensity at 400 nm could be ignored. In addition, since the added sodium borohydride largely exceeds the content of p-nitrophenol, the kinetics of the reduction can be treated as the first-order function of p-nitrophenol concentration [32,33] .…”
Section: Responsive Catalytic Activity Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift of the peak for the film towards the red region by about 20 nm, compared to the aqueous solution, is a common effect due to aggregation when a chromophore is incorporated within a polymeric film. [60] Unfortunately, UV-visible spectroscopy cannot directly detect the incorporation of palladium nanoparticles unambiguously as they do not display a strong surface plasmon band absorbance. [61] However, AFM, CV, and SECM data, reported in the following sections, confirmed the successful incorporation of Pd-DMAP nanoparticles.…”
Section: Uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…As a result, the long-chain polymer structure of fibrin induces the aggregation of the Au NPs (Scheme 1A). The polymers assemble around each particle, thereby keeping them apart or holding them together, depending on the relative sizes of the polymers to particles, the radius of the effective repulsion between the particles, and the initial conformation of the polymers (Aubouy and Raphaël, 1998;Boyer et al, 2010;Ding et al, 2007;Huang et al, 2004;Polavarapu and Xu, 2008;Rahme et al, 2007;Skirtach et al, 2007). The polymer size and concentration play crucial roles in determining the stability of the particles (Chaplain et al, 1995;Mayer, 2001).…”
Section: Resultsmentioning
confidence: 99%